2017
DOI: 10.3892/ol.2017.6570
|View full text |Cite
|
Sign up to set email alerts
|

Application of pirarubicin photosensitizer fluorescence cystoscopy in early detection of bladder cancer

Abstract: The aim of this study was to investigate the value of pirarubicin (THP) photosensitizer fluorescence cystoscopy for the early diagnosis of bladder cancer. From January 2012 to June 2015, 25 patients with painless gross hematuria, were injected with THP 15 min prior to surgery and subsequently underwent fluorescence cystoscopy examination. Locations of tumors were recorded and biopsies were performed (total of 109 biopsies) under white and fluorescence light guidance. Biopsies were conducted at the THP-positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In a study to determine the optimum dose of hypericin, 225 ug for 30 min was concluded to be the optimum dose for intravesical instillation ( 25 ). In addition, pirarubicin has also been used for PDD ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a study to determine the optimum dose of hypericin, 225 ug for 30 min was concluded to be the optimum dose for intravesical instillation ( 25 ). In addition, pirarubicin has also been used for PDD ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9] Traditional surgical techniques include open surgery and transurethral resection (TUR). 10,11 A recent meta-analysis showed that narrow band imaging-assisted TUR could reduce the rate of bladder cancer recurrence, compared with the rate following white light imaging TUR. 12 In recent years, advances in the use of holmium lasers have facilitated new approaches for such surgeries.…”
Section: Introductionmentioning
confidence: 99%